FAIR TRADE: TWO-WAY BILINGUAL EDUCATION - Lightbown, Patsy M. (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract One approach to bilingual education that has gained increasing support from parents, educators, and researchers in the United States is one in which English language learners and English proficient students share a classroom and receive instruction in both English and the dominant language of the English language learners. In most such two-way bilingual education programs, the stated goal is for both groups of students to learn each other’s language. In this paper, I briefly review the background to this approach.Following this, I present a case study of one such two-way bilingual program in which the student population came from Latino and African-American backgroundsSome of the Latino students were Spanishdominant while others knew little Spanish. The African-American students knew little or no Spanish when they arrived at school and, furthermore, many had limited experience with the variety of Standard American English spoken in the classroom. Students in the two-way bilingual education program did as well as or better than their peers who were being educated either in English-only classes or in transitional bilingual education classes. For students in the two-way program, Spanish reading ability for Spanish speakers developed at a faster rate than English reading ability for English speakers, and Spanish-dominant students did better in English than Englishdominant students did in Spanish. Data from classroom observation show that the formal assessment procedures were not able to capture much of the learning that took place in the classrooms. Nevertheless, the findings add to the evidence found in previous research that two-way bilingual education is an effective approach for both English proficient students and English language learners. Resumen Un enfoque empleado para la enseñanza bilingüe que viene recibiendo un respaldo cada vez mayor por parte de padres, educadores e investigadores de los EE.UU. consiste en la integración de aprendices de inglés y de usuarios nativos de la lengua, los cuales comparten aula y reciben enseñanza tanto en inglés como en la lengua dominante de los aprendices de inglés (español). En la mayoría de estos planes de enseñanza bilingüe de doble vía, el objetivo explícito es que cada grupo aprenda la lengua del otro. En este trabajo hago un breve repaso de los antecedentes de este enfoque y luego presento un estudio de caso que se basa en un plan bilingüe de doble vía en el cual el alumnado proviene de las comunidades latino y afroestadounidense. Algunos de los alumnos latinos tenían el español como lengua dominante mientras que otros sólo tenían conocimientos básicos de la lengua. Los alumnos afroestadounidenses tenían conocimientos básicos o nulos de español al inicio del plan; además, muchos tenían poca experiencia con la variedad de inglés estadounidense estándar que se usaba en el aula. Los alumnos del plan bilingüe de doble vía obtuvieron resultados iguales o superiores a los de sus compañeros que recibían clases impartidas bien sólo en inglés o de enseñanza bilingüe transitoria. En el caso de los alumnos del plan de doble vía, la destreza de lectura en español para los hispanohablantes se desarrolló con mayor rapidez que la destreza de lectura en inglés para los anglohablantes; además, los alumnos que tenían el español como lengua dominante obtuvieron mejores resultados en inglés que aquellos obtenidos en español por los alumnos que tenían el inglés como lengua dominante. Los datos de las observaciones de clase muestran que los procedimientos formales de evaluación no fueron capaces de captar una buena parte del aprendizaje que tenía lugar en el aula. Sin embargo, los resultados se suman a las pruebas provenientes de investigaciones previas que indican que la enseñanza bilingüe de doble vía es un enfoque eficaz tanto para usuarios nativos como para aprendices del inglés.